Fibrosis—the tale of H3K27 histone methyltransferases and demethylases - Basta, Morgan D.; Petruk, Svetlana; Mazo, Alexander; Walker, Janice L. (Frontiers in Cell and Developmental Biology, 2023)
Fibrosis, or excessive scarring, is characterized by the emergence of alpha-smooth muscle actin (αSMA)-expressing myofibroblasts and the excessive accumulation of fibrotic extracellular matrix (ECM). Currently, there is a lack of effective treatment options for fibrosis, highlighting an unmet need to identify new therapeutic targets. The acquisition of a fibrotic phenotype is associated with changes in chromatin structure, a key determinant of gene transcription activation and repression. The major repressive histone mark, H3K27me3, has been linked to dynamic changes in gene expression in fibrosis through alterations in chromatin structure. H3K27-specific homologous histone methylase (HMT) enzymes, Enhancer of zeste 1 and 2 (EZH1, EZH2), which are the alternative subunits of the Polycomb Repressive Complex 2 (PRC2) and demethylase (KDM) enzymes, Ubiquitously transcribed tetratricopeptide repeat, X chromosome (UTX), and Lysine demethylase 6B (KDM6B), are responsible for regulating methylation status of H3K27me3. In this review, we explore how these key enzymes regulate chromatin structure to alter gene expression in fibrosis, highlighting them as attractive targets for the treatment of fibrosis.